COMPARISON OF ANTHOCYANIN STABILITY OF ETHANOL EXTRACT Etlingera elatior (Jack) R.M. Sm. WITH COOPIGMENTATION OF TARTRIC ACID AND GALIC ACID - Lilis Tuslinah; Firman Gustaman; Desi Silviani; Mira Rohimah (Universitas Muhammadiyah Magelang, 2021)
Anthocyanins are unstable compounds mainly due to the influence of pH and temperature, including those sourced from the Honje Laka fruit (Etlingera elatior (Jack) R.M.Sm), to increase its stability, copigmentation method is used. In this study, the stability of anthocyanins was compared after being copigmented with tatric acid and gallic acid through the value of % color retention of anthocyanins using the UV-VIS Spectrophotometry method. Based on the test results, copigmentation with tartaric acid ratio 1: 75 mmol and gallic acid 1: 100 nmol is the optimal ratio to stabilize anthocyanins at pH 2 at 300C. Optimal conditions of copigmentation with tartaric acid and gallic acid did not give a significant difference at pH 2 temperature 300C